Monitoring The Water Quality Of The Klawing River In Purbalingga Regency Using The Pollution Index And Storet Methods - Afrilia Nur Fajriyah; Arini Inayatul Wafiroh; Arif Nur Surdianto; Aulia Firda Alfiana (Applied Environmental Sustainability and Technology, 2026)
Monitoring river water quality is important because increasing anthropogenic activities can degrade aquatic environments. However, studies combining water quality parameter analysis with two assessment methods, namely the Pollution Index (PI) and Storet, remain limited, especially in the Klawing River, Purbalingga Regency. This study aims to analyze the water quality of the Klawing River using physical and chemical parameters and to determine its status using the Pollution Index and Storet methods. This study used a descriptive quantitative approach. Sampling was conducted at three locations representing the upstream, residential, and downstream areas. The observed parameters included temperature, Total Dissolved Solids (TDS), pH, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), and Chemical Oxygen Demand (COD). The data were compared with water quality standards outlined in Government Regulation No. 22 of 2021 and analyzed using the Pollution Index and Storet methods. The results show that physical parameters still meet the quality standards. However, chemical parameters indicate water quality degradation, particularly low DO levels of 1.15-1.7 mg/L and high COD levels of 36.4-60.2 mg/L. The Pollution Index method classified the river as lightly polluted, while the Storet method classified it as moderately polluted. Therefore, integrated pollution control is needed to maintain the sustainability of the Klawing River.